A catalog of the Brachystomatidae of Chile (Diptera: Empidoidea) - González, Christian R.; Elgueta, Mario; Rafael, José Albertino (Zootaxa, 2021)
A catalog of the Brachystomatidae of Chile is provided. We present all valid names and synonyms for the 36 species and five genera distributed in the country, including information about name, author, year of publication, page number, type species, type depository, type locality and references. Heterophlebus Philippi is the richest genus in Chile, with 16 species, followed by Apalocnemis Philippi with 11 species, Ceratomerus Philippi with seven and Gondwanamyia Sinclair, Cumming, Brooks, Plant & Saigusa and Hyperperacera Collin with one species each. The geographical distribution of the different species was compiled from bibliographic data and revised collections.